Five‐year outcomes of ADHD diagnosed in adulthood. Issue 1 (20th November 2020) - Nylander, Elin; Floros, Orestis; Sparding, Timea; Rydén, Eleonore; Hansen, Stefan; Landén, Mikael
Abstract : There is a dearth of long‐term follow‐up studies of adults diagnosed with ADHD. Here, the aim was to evaluate long‐term outcomes in a group of ADHD patients diagnosed in adulthood and receiving routine psychiatric health care. Adults diagnosed with any type of ADHD ( n = 52) and healthy controls ( n = 73) were assessed at baseline and at a 5‐year follow‐up, using Global Assessment of Functioning (GAF), Clinical Global Impression (CGI), Brown ADD Scale (BADDS) and Adult ADHD Self‐Report Scale (ASRS). A multivariate regression method was used to identify factors predicting 5‐year outcomes, including baseline ratings, medication intensity, comorbidity, intelligence quotient (IQ), age, and sex. After 5 years, ADHD patients reported fewer and/or less severe symptoms compared to baseline, but remained at clinically significant symptom levels and with functional deficits. Baseline self‐reports of ADHD symptoms predicted their own 5‐year outcome and low baseline functioning level predicted improved global functioning at follow‐up. Factors previously reported to predict short‐term outcomes (i.e., medication, comorbidity, IQ, age, and sex) did not anticipate long‐term outcomes in present study.